1988
DOI: 10.1037/0735-7044.102.3.349
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal and amygdaloid involvement in working memory for nonspatial stimuli.

Abstract: Hippocampal lesions in rats lead to an impairment of performance in spatial delayed conditional discriminations. The effect of such lesions on nonspatial tasks is controversial. In monkeys, both the hippocampus and the amygdala are involved in nonspatial delayed conditional discriminations. The effect of amygdaloid lesions in rats on this type of task has not been studied. To clarify the role of hippocampus and amygdala in a cue-relevant/space-irrelevant delayed conditional discrimination, rats were trained on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
87
4
1

Year Published

1991
1991
1999
1999

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 146 publications
(105 citation statements)
references
References 27 publications
13
87
4
1
Order By: Relevance
“…Rats with hippocampal lesions have substantial and enduring deficits in some nonspatial working memory tasks (Jagielo, Nonneman, Isaac, & Jackson-Smith, 1990;Olton & Feustle, 1981;Raffaele & Olton, 1988) but not in all (Aggleton, Blindt, & Rawlins, 1989;Aggleton et al, 1986;Mumby, Wood, & Pinel, 1992;Rothblat & Kromer, 1991;Shaw & Aggleton, 1993). We have previously reported that the critical factors determining whether or not these lesions affect object matching or noumatching to sample are the size complexity, and repetitious use of the stimuli (Cassaday & Rawlins, 1995;Rawlins et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Rats with hippocampal lesions have substantial and enduring deficits in some nonspatial working memory tasks (Jagielo, Nonneman, Isaac, & Jackson-Smith, 1990;Olton & Feustle, 1981;Raffaele & Olton, 1988) but not in all (Aggleton, Blindt, & Rawlins, 1989;Aggleton et al, 1986;Mumby, Wood, & Pinel, 1992;Rothblat & Kromer, 1991;Shaw & Aggleton, 1993). We have previously reported that the critical factors determining whether or not these lesions affect object matching or noumatching to sample are the size complexity, and repetitious use of the stimuli (Cassaday & Rawlins, 1995;Rawlins et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…We did not specifically investigate delay dependence because we continue to observe a robust effect of hippocampal lesions on DNMS with large boxes when testing with the minimum delay required to switch box positions (cf. Raffaele & Olton, 1988). The fact that deficits in conventional tests of spatial memory are not typically delay dependent either (cf.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations